2014
DOI: 10.1016/j.phrs.2014.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Structural determinants of peripheral O-arylcarbamate FAAH inhibitors render them dual substrates for Abcb1 and Abcg2 and restrict their access to the brain

Abstract: The blood-brain barrier (BBB) is the main entry route for chemicals into the mammalian central nervous system (CNS). Two transmembrane transporters of the ATP-binding cassette (ABC) family – Breast Cancer Resistance Protein (ABCG2 in humans, Abcg2 in rodents) and P-glycoprotein (ABCB1 in humans, Abcb1 in rodents) – play a key role in mediating this process. Pharmacological and genetic evidence suggests that Abcg2 prevents CNS access to a group of highly potent and selective O-arylcarbamate fatty-acid amidohydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
1
5
0
1
Order By: Relevance
“…The mechanism underlying this peripheral segregation has been shown to involve two distinct transmembrane transporters that belong to the ATP‐binding cassette family: Abcg2 (breast cancer resistance protein) and Abcb1 (P‐glycoprotein) . These transporters are highly expressed in cells of the blood–brain barrier and may act in concert to restrict the access of URB937 to the brain and spinal cord . Supporting this idea, in the present report we confirmed that URB937 does not enter the CNS when administered at therapeutically effective doses (Figures a and b).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The mechanism underlying this peripheral segregation has been shown to involve two distinct transmembrane transporters that belong to the ATP‐binding cassette family: Abcg2 (breast cancer resistance protein) and Abcb1 (P‐glycoprotein) . These transporters are highly expressed in cells of the blood–brain barrier and may act in concert to restrict the access of URB937 to the brain and spinal cord . Supporting this idea, in the present report we confirmed that URB937 does not enter the CNS when administered at therapeutically effective doses (Figures a and b).…”
Section: Discussionsupporting
confidence: 83%
“…Confirming previous work, we found that the compound is excluded from the CNS (Figures and ). The mechanism underlying this peripheral segregation has been shown to involve two distinct transmembrane transporters that belong to the ATP‐binding cassette family: Abcg2 (breast cancer resistance protein) and Abcb1 (P‐glycoprotein) . These transporters are highly expressed in cells of the blood–brain barrier and may act in concert to restrict the access of URB937 to the brain and spinal cord .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…31 Various studies have also demonstrated that Tween 80-based NPs could inhibit the exocytosis of p-gp, increasing the concentration of chemotherapeutics in tumor cells. 32 In this study, PLGA-Tween 80 conjugate was first synthesized via a one-step esterification reaction. The chemical structure of PLGA-Tween 80 was confirmed by 1 H-NMR and FTIR spectra.…”
Section: Results and Discussion Characterization Of Synthesized Copolmentioning
confidence: 99%
“…Az apicalistól a basolateralis és az ellentétes irányú transzportot értékelték inhibitorok jelenlétében és hiányában [17]. Moreno-Sanz és mtsai [18] Bcrp-t overexpresszáló MDCKII sejtvonalon vizsgálták zsírsav-amidohidroláz-gátlók penetrá cióját. Minocha és mtsai [19] szintén MDCKII sejteken tanulmányozták a P-gp-és Bcrp-moduláció hatásait.…”
Section: Vizsgálati Módszerekunclassified